2013
DOI: 10.1038/npp.2013.11
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism of Rapidly Reversible Cerebral Ventricular Enlargement Independent of Tissue Atrophy

Abstract: Ventricular enlargement, a common in vivo marker of aging, disease, and insult, is presumed to reflect atrophy of surrounding brain regions. Pathological mechanisms underlying ventricular enlargement, however, are likely specific to the condition under investigation. Here, multimodal imaging, incorporating structural magnetic resonance imaging (MRI), MR spectroscopy (MRS), and diffusion weighted imaging (DWI), was used in rats exposed to binge ethanol (EtOH) to provide insight into a mechanism of reversible ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 49 publications
5
55
0
Order By: Relevance
“…Results of in vivo MR imaging are consistent with our previous studies: each binge EtOH exposure cycle was associated with an increase in the volume of the lateral ventricles, a decrease in the levels of NAA and tCr, and an increase in the levels of Cho (Zahr et al, 2010; Zahr et al, 2014; Zahr et al, 2013). As described in great detail, this pattern of changes is consistent with a model of transient fluid redistribution during acute EtOH intoxication and recovery (Zahr et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results of in vivo MR imaging are consistent with our previous studies: each binge EtOH exposure cycle was associated with an increase in the volume of the lateral ventricles, a decrease in the levels of NAA and tCr, and an increase in the levels of Cho (Zahr et al, 2010; Zahr et al, 2014; Zahr et al, 2013). As described in great detail, this pattern of changes is consistent with a model of transient fluid redistribution during acute EtOH intoxication and recovery (Zahr et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Our in vivo magnetic resonance (MR) studies have consistently shown that a single 4-day EtOH binge is associated with reversible brain abnormality: enlargement of lateral ventricles, reductions in MR Spectroscopy (MRS)-detectable metabolites, N-acetyl-asparate (NAA) and total creatine (tCr), and elevations in choline-containing compounds (Cho) (Zahr et al, 2010; Zahr et al, 2014; Zahr et al, 2013). Together, these reversible events indicate transient cellular injury.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of changes at time 2 included enlarged ventricles, hyperintensities in the inferior colliculus, and reduced NAA and Cho in the thalamus, but no lactate elevation. Enlargement of the ventricles has previously been reported in thiamine deficiency (Dror et al, 2010), but this MR metric is a non-specific index of brain pathology (e.g., Zahr et al, 2013). The edematous nature of inferior collicular pathology (Watanabe and Kanabe, 1978) may explain why it is detected early in the course of in thiamine deficiency by in vivo MRI, which is sensitive to brain pathology caused by tissue edema (Jung et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Magnetic resonance imaging is acquired 1) pre-exposure (i.e., baseline), 2) within 2h of the last alcohol dose (BALs 250–300 mg/dL), and 3) after 7 days of recovery. The alcohol insult is reflected by reliably and significantly increased lateral ventricular volume in the alcohol group compared with the control group (Figure 4) (Zahr et al, 2010; Zahr et al, 2013a; Zahr et al, 2013b). Alcohol relative to control animals furthermore reveal alterations in MR spectroscopy (MRS) derived signals: lower N-acetylaspartate (NAA) and total creatine (tCr) and higher choline-containing compounds (Cho) (Zahr et al, 2010; Zahr et al, 2013a; Zahr et al, 2013b).…”
Section: Cognitive Function Deficit and Recoverymentioning
confidence: 98%
“…Lack of tissue volume reductions in brain regions adjacent to ventricles argues against atrophy as a mechanism of ventricular expansion. Decreased tissue water T2, decreased thalamic diffusivity, and a role for both NAA and Cho as osmolytes support a mechanism of rapid fluid redistribution during alcohol intoxication to account for rapid ventricular volume changes (Zahr et al, 2013b). Shifts of fluid between various brain compartments might explain reversibility of ventricular enlargement observed in humans following recovery from alcohol abuse (Zipursky et al, 1989), anorexia nervosa (Enzmann and Lane, 1977), and prolonged steroid use (Bentson et al, 1978).…”
Section: Cognitive Function Deficit and Recoverymentioning
confidence: 99%